Social Values for Determination of Social Carrying Capacity - Rusli, M; Avenzora, R; Sunarminto, T; Malihah, E (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Tourism planning and development, if not suitable with sustainability direction become useless from all points of view. Sustainability in meant not only emphasizing to availability healthy natural environment. Community social acceptance become one of the keys, where the sustainability of The Triple Bottom Line keeps emphasizing people to push the sustainability of profit and planet. Society of this level not only a few who have the ability but whole society who have a will and potential must be pushed to get involved. The purpose of research is to give recommendations of assessment indicators related to tourism social carrying capacity optimization model by the principles of sustainable. The selected research method is the combination of qualitative research. Source data is obtained by data observation directly in the field using interview data collection techniques. That primer data is reinforced by secondary data related to the research title. The approach is carried out through the basic values of life as a forming factor for social interaction. Several indicators presented by key informants agreed that the relationship created by communication and action became the basis for understanding the social value system itself. The interesting thing about understanding interactions is that the relationships that are formed are not only in a tourism destination, but are made possible through networks. In addition, some understandings do not only form positive things, in some cases negative situations occur.